2018
DOI: 10.1186/s12941-018-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of virulence gene expression with colistin-resistance in Acinetobacter baumannii: analysis of genotype, antimicrobial susceptibility, and biofilm formation

Abstract: BackgroundAcinetobacter baumannii causes difficult-to-treat nosocomial infections, which often lead to morbidity due to the development of antimicrobial drug resistance and expression of virulence genes. Data regarding the association of resistance to colistin, a last treatment option, and the virulence gene expression of A. baumannii is scarce.MethodsWe evaluated the MLVA genotype, antimicrobial resistance, and biofilm formation of 100 A. baumannii isolates from burn patients, and further compared the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
4
17
2
Order By: Relevance
“…The predominance of IC II was in good agreement with previous reports from Japan 52 and Brazil 53 that recognized the IC II as the most common clone in A. baumannii isolates. Meanwhile, the prevalence of IC I with 11.4% frequency rate was lower than the frequency rate (19%) stated by Bahador et al 54 in Tehran, Iran. Another difference between this and that study was the strong biofilm production by the majority of our CI I and CI II lineages, while in the Bahador's study, 54 they were moderate biofilm producers.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The predominance of IC II was in good agreement with previous reports from Japan 52 and Brazil 53 that recognized the IC II as the most common clone in A. baumannii isolates. Meanwhile, the prevalence of IC I with 11.4% frequency rate was lower than the frequency rate (19%) stated by Bahador et al 54 in Tehran, Iran. Another difference between this and that study was the strong biofilm production by the majority of our CI I and CI II lineages, while in the Bahador's study, 54 they were moderate biofilm producers.…”
Section: Discussioncontrasting
confidence: 56%
“…Meanwhile, the prevalence of IC I with 11.4% frequency rate was lower than the frequency rate (19%) stated by Bahador et al 54 in Tehran, Iran. Another difference between this and that study was the strong biofilm production by the majority of our CI I and CI II lineages, while in the Bahador's study, 54 they were moderate biofilm producers.…”
Section: Discussioncontrasting
confidence: 56%
“…This theory is partly supported by the fact that the over expression of MexAB-OprM and MexXY-OprM efflux pumps has already been linked to resistance in P. aeruginosa in multiple antimicrobial agents such as aminoglycosides (Hocquet et al, 2003). One interesting study done by Bahador et al (2018) found that resistance to colistin in A. baumannii isolates is linked to the increase in virulence factors such as biofilm formation in burn patients. This renders the treatment of such MDR more challenging, as both resistance to colistin and virulence factors must be tackled at once (Bahador et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…One interesting study done by Bahador et al (2018) found that resistance to colistin in A. baumannii isolates is linked to the increase in virulence factors such as biofilm formation in burn patients. This renders the treatment of such MDR more challenging, as both resistance to colistin and virulence factors must be tackled at once (Bahador et al, 2018). Furthermore, two studies reported the isolation of colistin resistant A. baumannii and K. pneumoniae with mutations in the pmrB and mgrB genes, respectively (Haeili et al, 2017, 2018) (Table 3).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…6 There are now reports from different regions of the world of pan-drug-resistant (PDR) A. baumannii. 7 The primary resistance mechanism is mediated through the modification of the lipid A moiety of lipopolysaccharide (LPS) through the addition of phosphoethanolamine (PEtN) through overexpression and/or mutations in the two-component regulatory system PmrA and PmrB. Other mechanisms have been described and include the loss of LPS caused by either insertional inactivation of lipid A biosynthesis genes or mutations, but this appears to be limited to in-vitro studies.…”
Section: Introductionmentioning
confidence: 99%